Analisis Pengaruh Kenaikan Harga BBM Terhadap Pergerakan Saham Sektor Transportasi dan Logistik - Tanza, Alifia; Maulidya, Rizka Putri; Junita, Tarisya Permata; Widodo, Edy (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
The capital market or also known as the stock exchange is one of the financial market activities, which carry out economic activities and financial functions, where the activities carried out on the stock exchange are very dependent on government policy. On April 1, the government issued a new policy, which was an increase in the price of Pertamax fuel oil. Although the dynamics of the capital market were not directly affected, the increase in fuel prices could not be separated from stock market activity. This research was conducted with the intention of seeing whether there was a stock market reaction, especially shares in the transportation and logistics sector, to the increase in fuel prices on April 1, 2022. This study used the Abnormal Return (AR) and Trading Volume Activity (TVA) variables. ) with a period of 30 days, before and after the notification of the increase in fuel prices. The method used is to use the Wilcoxon test. From this study, it was found that the capital market did not react to the policy of increasing fuel prices. This can be seen from the absence of differences in AR and TVA, before and after the notification of the increase in fuel prices.